Language and Dialect between Modern and Ancient [In Arabic] - Bouam, Nadjat (Milev Journal of Research and Studies, 2022)
The ancient and modern Arab linguists differed in defining and adjusting the concept of language and dialect and the difference between them?, and how did the classical arise?, and through this research I will present these points in some detail, to reach the conclusion that linguists are old despite the great services they have provided to preserve and control the Arabic language, but they neglected all dialects and only received various references and phrases in the books of language, literature and history, which makes it impossible to study them, by virtue of their study. The changing nature of the dialect from time to time, unlike modern linguists who knew the importance of dialects in the field of linguistic lesson, and their usefulness in understanding the nature of classical, they accepted to study them to know the characteristics common to them and the classical.